Coastal management integrating science, engineering and management : proceedings of the international conference organized by the Institution of Civil Engineers and held in Bristol, UK, on 22-23 September 1999 - Fleming, C. A. (Thomas Telford, 2000)
Covers coastal management issues including, planning and implementation, economic evaluation, the contribution of technology, legal and geomorphic impacts, and managing risk and uncertainty. This book is a useful reference for those involved in coastal management.